Analisis Pengaruh Gaya Hidup Mahasiswa terhadap Indeks Prestasi Kumulatif (IPK) Menggunakan Model Regresi - Sastra, Amner; Sabri, Khairul; Yanto, Budi; Asmen, Faisal; Inal, Inal; Crisdianto, Ahlul (KERNEL: Jurnal Riset Inovasi Bidang Informatika dan Pendidikan Informatika, 2023)
Student lifestyle plays an important role in determining academic performance, including the Grade Point Average (GPA). This study aims to analyze the impact of lifestyle on students' GPA using a quantitative approach with regression analysis. Data were collected through questionnaires covering aspects such as sleep patterns, dietary habits, physical activity, and study habits. After data preprocessing, the residual normality test showed that the data met the normal distribution assumption, with a p-value of 0.1373 from the Shapiro-Wilk test. The constructed regression model was evaluated using Mean Squared Error (MSE), Root Mean Squared Error (RMSE), and the coefficient of determination (R²). The results showed that lifestyle significantly affects GPA, particularly study habits and sleep patterns. Understanding these factors can help students optimize their lifestyles to improve academic performance. These findings can serve as a foundation for educational institutions in designing support programs for students.